Between Punishment And Discipline: Student Perceptions And The Application Of Punishment Toward Student Discipline - Mulyati, Mulyati; Uyun, Muhamad (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research seeks to determine the relationship between student perceptions and the implementation of punishment in student discipline. This research employed a correlational quantitative approach. The research involved 131 eleventh-grade students of Palembang's senior high school. This research used a purposive sampling technique. The data was analyzed using multiple linear regression with IBM SPSS software version 22.0 for Windows. This research collected data using three scales: student perception, punishment, and discipline. The major hypothesis test yielded rx12-y = 0.601, F = 36.232, and sig < 0.05, indicating that student perceptions and punishment can predict discipline among eleventh-grade high school students in Palembang. Therefore, students' perceptions of discipline and punishment constitute an effective 36.1% contribution to student discipline, with the remaining 63.9% influenced by variables outside of the research. The first hypothesis test yielded rx1-y = 0.251 with a significance level of <0.05. It means there is a significant positive influence between student perceptions and discipline among eleventh-grade high school students in Palembang, with a 29% effective contribution to punishment. The second hypothesis test yielded rx2-y = 0.499, with a significance level of <0.05. It means that the punishment significantly positively influences student discipline among eleventh-grade high school students in Palembang, with an effective contribution of 7%.Keywords: Student Perception, Punishment, Student Discipline